(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Biostatistics is largely concerned with Mathematicians Statisticians who work in the biologicalsciences. Biometrical procedures are used frequently by biologists physicians. Multivariate statisticalanalysis concerns in understanding different aims and background of each of the different forms ofmultivariate regression models and how they relate to each other. Any data study including the descriptionof the connection between a response variable and one or more explanatory factors has used regressionmethods. There exists sufficient literature on applications of Multivariate Statistical tools inBiostatistics. Presently, it has been observed from the literature on Multivariate statistical techniquesthat Multivariate Logistic regression analysis and Poisson regression analysis have become, in manyapplications, the standard methods of analysis in Biostatistics